Global, regional, and national burden of tobacco-related neurological disorders from 1990 to 2021: Trends and future projections - Chenyang Zhang; Zhihan An; Jixuan Jiang; Jingyi Ge; Wanqiong Huang; Jialin Pei; Yiyao Liu; Jiayu Yao; Zirui Guo; Xuanxi Liu; Yanhui Cui (Tobacco Induced Diseases)
Introduction Tobacco use is as a major public health concern around the world, adversely impacting quality of life. Our study aims to analyze the trends in the burden of tobacco-related neurological disorders (ND) at global, regional, and national levels from 1990 to 2021, as well as potential future trends.